Young people's everyday pathways into drug harms in Shan State, Myanmar. Issue 11 (2nd November 2022) - Meehan, Patrick; Sadan, Mandy; Aung Hla, Sai; Kham Phu, Sai; Muai Oo, Nang
Abstract: In recent decades, youth drug use has become a cause of increasing concern across Asia and has inspired hardening drug control measures. However, consistently missing from drug narratives is a deeper engagement with young people themselves on why they use drugs and an understanding of the social, political, economic and cultural forces that shape their interactions with drugs. By engaging with the lived experiences of young people in the Myanmar city of Taunggyi, this paper offers new insights into the everyday pathways and practices through which systemic risk factors – poverty, large-scale local drug production and poor welfare provision – materialise into drug harms. This paper draws attention to three factors that shape these pathways: first, the role that drug-selling and drug consumption plays in the coping strategies that people deploy in an environment of economic hardship; second, the intersections between drug use and gendered conceptions of youth; and, third, the everyday institutional practices of local authorities. Exploring young people's testimonies offers a grounded perspective for considering what can be done to reduce drug harms in a context where the structural determinants of drug risks are deeply entrenched and, in the context of post-coup Myanmar, likely to worsen.